Knowledge of COVID-19 and Compliance in Preventing the Diseases on Nursing Students in Indonesia - Alfianur, Alfianur (Gaceta Médica de Caracas, 2022)
Coronavirus Disease (COVID-19) is a disease with respiratory tract infection symptoms experienced by almost all countries worldwide. The government has conveyed the prevention of this disease many times. However, the success of prevention depends on the discipline and compliance of the community in carrying out the government’s appeal. This study aimed to analyze the relationship between the level of knowledge with adherence to COVID-19 prevention.